Playing gamelan bonang in the air: user requirements for designing a digital musical instrument for the Malay bonang - Ahmad Saffian, Khatriza; Mohd Norowi, Noris; Abdullah, Lili Nurliyana; Sulaiman, Puteri Suhaiza; Musib, Ahmad Faudzi (Universiti Pendidikan Sultan Idris, 2024)
In recent years, computer technologies have been impactful in the design and development of Digital Musical Instruments (DMIs). As music interaction became prominent in the Human-Computer Interaction (HCI) field, emphasis on user requirement upon the design of musical interfaces has also grown since the last decade. Although designing new DMIs is becoming very popular, it is often determined by the designers and often not reflective of users’ needs. In this study, we explored user requirements for the design of a virtual musical instrument of the Malay bonang, an instrument found in the Malay gamelan ensemble. The requirements were elicited from a group of gamelan experts to establish the bonang playing techniques to be mapped to the virtual instrument which we called Air Bonang. Findings revealed that in designing the Air Bonang that is natural and expressive, the fundamental playing techniques of the bonang should be integrated into the system using mid-air interaction. In addition, exploratory techniques might also be integrated into the Air Bonang to leverage musical expression. The outcome of the study proposes design criteria that encompass three aspects of a natural Air Bonang, namely, embodiment, expressiveness, and feedback.